The Effectiveness of Principal Leadership and Discipline on Teacher Performance in PPG Unwidha Klaten Partner Schools - Tukiyo; Sri Suwartini; Putri Zudhah Ferryka (Journal for Lesson and Learning Studies, 2025)
The variation in teacher performance influenced by the effectiveness of the principal's leadership and the application of discipline in PPG partner schools Unwidha Klaten is a problem that must be faced. This study aims to analyze the influence of principal leadership and discipline on teacher performance and compare the differences in partner and non-partner schools. The study uses a quantitative approach with an explanatory survey method. The subjects of the study were teachers at PPG partner schools Unwidha Klaten who were selected through purposive sampling techniques. Data was collected using a Likert scale questionnaire that has been tested for validity and reliability. Data analysis was carried out through classical assumption tests, simple and multiple linear regressions, and determination coefficient tests with the help of the SPSS program. The results showed that principals' leadership and discipline had a significant effect on improving teacher performance, where the influence was greater in PPG's partner schools than in non-partner schools. These findings confirm that effective leadership and a consistent discipline culture can improve motivation, professionalism, and learning quality. The implication of this study is the need to strengthen the leadership competence of school principals and the implementation of a culture of discipline in schools as a strategy to improve the quality of education, especially in supporting the success of the PPG program in producing professional teachers.